Equality & excellence in ancient and modern political philosophy - Frankel, Steven, 1968-; Ray, John A., 1957- (State University of New York Press, 2023)
Interpretations of critically important texts in political philosophy from Greek antiquity to modern times on the tension between human excellence and equality and its possible resolution.